The Somme - Prior, Robin; Wilson, Trevor, 1928- (Yale University Press, 2005)
"In the long history of the British Army, the Battle of the Somme was its bloodiest encounter. Between 1 July and mid-November 1916, 432,000 of its soldiers became casualties -- about 3,600 for every day of battle. German casualties, it is estimated, were far fewer -- probably 230,000 -- even though the British possessed superiority in the air and in artillery, the most lethal weapon on the Western Front." "What went wrong for the British, and who was responsible? Robin Prior and Trevor Wilson have examined the entire public archive covering the Somme campaign in 1916 and reconstruct the day-by-day course of the war. The colossal rate of infantry casualties was not the result of defects in the infantry itself, but the inadequacy of the fire support. Responsibility for tactical mistakes was not that of the brigadiers or divisional commanders, but of the High Command and the civilian War Committee. Field-Marshall Haig is shown as repeatedly deficient in strategy, tactics, command and organisation." "Hundreds of thousands of soldiers lay down their lives in a campaign which lacked both a coherent military plan and responsible political leadership."--Jacket